2020
DOI: 10.3390/ma13225297
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study of Sulfonated Co-Polynaphthoyleneimide Proton-Exchange Membrane for a H2/Air Fuel Cell

Abstract: The sulfonated polynaphthoyleneimide polymer (co-PNIS70/30) was prepared by copolymerization of 4,4′-diaminodiphenyl ether-2,2′-disulfonic acid (ODAS) and 4,4’-methylenebisanthranilic acid (MDAC) with ODAS/MDAC molar ratio 0.7/0.3. High molecular weight co-PNIS70/30 polymers were synthesized either in phenol or in DMSO by catalytic polyheterocyclization in the presence of benzoic acid and triethylamine. The titration reveals the ion-exchange capacity of the polymer equal to 2.13 meq/g. The membrane films were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…At higher hydration degrees, the environment of cations in membranes becomes similar to that for aqueous solutions of their salts, and the NMR chemical shifts approach these for aqueous solutions. The energy of interactions of large cesium cations with water molecules is insufficient to destroy the network of hydrogen bonds of water molecules, and the dependence of the 133 Cs chemical shift values on hydration degree is not pronounced [96,98]. This conclusion correlates well with dependences of 1 H chemical shifts on hydration degree [99,100].…”
Section: Hydration and Mobility Of Cations In Membranesmentioning
confidence: 51%
See 1 more Smart Citation
“…At higher hydration degrees, the environment of cations in membranes becomes similar to that for aqueous solutions of their salts, and the NMR chemical shifts approach these for aqueous solutions. The energy of interactions of large cesium cations with water molecules is insufficient to destroy the network of hydrogen bonds of water molecules, and the dependence of the 133 Cs chemical shift values on hydration degree is not pronounced [96,98]. This conclusion correlates well with dependences of 1 H chemical shifts on hydration degree [99,100].…”
Section: Hydration and Mobility Of Cations In Membranesmentioning
confidence: 51%
“…The correctness of these conclusions is proved by the fact that the diffusion coefficients for aqueous solutions of alkali metal chlorides, determined using both methods, are equal and close to the values found by NMR for membranes samples [ 107 ]. It should also be mentioned that the type of ion-exchange membrane significantly affects the ratio of the diffusion coefficients measured using NMR spectroscopy and conductivity [ 133 ].…”
Section: Ion Transfer In H + -Forms Of Membranementioning
confidence: 99%
“…22,39−42 We studied the temperature dependence of the self-diffusion coefficients for co-PNIS with the composition ODAS/MDAC = 70/30, which was wetted at 100% humidity. 43 It was found that D NMR has a similar temperature dependence in co-PNIS 70/30 and in Nafion with activation energies of 0.24 eV above and 0.32 eV below a crossover at T cr = 253 K. We expect that a variation of the ratio of the hydrophilic to hydrophobic polymer groups allows us to modify the diffusion pathways for water and, thus, the transport characteristics, as was observed for some other hydrocarbon-based membranes. 44−46 The goal of this work is to determine the dependence of the proton self-diffusion coefficients in co-PNIS polymers on the ratio of hydrophilic to hydrophobic groups at 100% humidity in a wide temperature range.…”
Section: Introductionmentioning
confidence: 67%
“…The chemical structure of co-polynaphthoylenimides based on MDAC, NTDA, and ODAS has been described in detail in our previous publications. 27,43,47,48 For the preparation of co-PNIS polymer films, the chemical components ODAS (0.5044 g, 0.0014 M), MDAC (0.1718 g, 0.0006 M), NTDA (0.5364 g, 0.002 M), benzoic acid catalyst (0.34 g, 0.0028 M), triethylamine solubilizer of ODAS (0.303 g, ∼0.003 M), and phenol or DMSO as solvents (10.0 g) were placed in a three-piece flask equipped with a stirrer and a capillary for introducing argon. 26,47 The reaction mass mixture was heated in an argon flow to 80 °C while stirring until all monomers were dissolved.…”
Section: Synthesis Of Co-pnis Membranesmentioning
confidence: 99%
See 1 more Smart Citation